Polymerase Spiral Reaction Assay for Rapid and Real Time Detection of West Nile Virus From Clinical Samples - Tomar, Priyanka Singh; Kumar, Jyoti S.; Patel, Sapan; Sharma, Shashi (Frontiers in Cellular and Infection Microbiology, 2020)
West Nile virus (WNV) is a mosquito-borne virus of public health importance. Currently, there is no FDA approved vaccine available against WNV infection in humans. Therefore, the early diagnosis of the WNV infection is important for epidemiologic control and timely clinical management in areas where multiple Flaviviruses are endemic. The present study aimed to develop reverse transcription polymerase spiral reaction (RT-PSR) assay that rapidly and accurately detects the envelope (env) gene of WNV. RT-PSR assay was optimized at 63°C for 60 min using real-time turbidimeter or visual detection by the addition of SYBR Green I dye. The standard curve for RT-PSR assay was generated using the 10-fold serial dilutions of in vitro transcribed WNV RNA. To determine the detection limit of RT-PSR assay, an amplified product of conventional RT-PCR was in vitro transcribed as per standard protocol. The detection limit of the newly developed RT-PSR assay was compared with that of conventional RT-PCR and CDC reported TaqMan real-time RT-PCR using a serial 10-fold dilution of IVT WNV RNA. The detection limit of RT-PSR was found to be 1 RNA copy, which is 100-fold higher than that of conventional RT-PCR (100 copies). This suggests that RT-PSR assay is a valuable diagnostic tool for rapid and real-time detection of WNV in acute-phase serum samples. The assay was validated with a panel of 107 WNV suspected human clinical samples with signs of acute posterior uveitis and onset of febrile illness. Out of 107 samples, 30 were found positive by RT-PSR assay. The specificities of the selected primer sets were established by the absence of cross-reactivity with other closely related members viruses of the Flaviviruses, Alphaviruses, and Morbilliviruses groups. No cross-reactivity was observed with other viruses. To best of our knowledge, this is the first report describing the RT-PSR assay for the detection of RNA virus (WNV) in clinical samples. RT-PSR is a high throughput method and more than 30 reactions can be run at once in real-time turbidimeter. PSR assay has potential to be used for a rapid screening of large number of clinical samples in endemic areas during an outbreak.